2014
DOI: 10.1016/j.actpsy.2014.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Redundancy gain in semantic categorisation

Abstract: Redundancy gain refers to the performance enhancements often associated with the presentation of redundant versus single targets (for example, faster, more accurate, or more forceful responses). Though predominantly observed in relatively simple tasks (e.g., stimulus detection), there have been some efforts to investigate similar phenomena in tasks involving higher level processing. We conducted three experiments aimed at determining (a) whether a redundancy gain would be evident in a task unambiguously requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 105 publications
(284 reference statements)
0
6
0
Order By: Relevance
“…The first such study found no redundancy gains and concluded that capacity is limited, potentially (but not necessarily) due to a serial process (Mullin & Egeth, 1989). However, later studies reported contradictory results (Shepherdson & Miller, 2014, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…The first such study found no redundancy gains and concluded that capacity is limited, potentially (but not necessarily) due to a serial process (Mullin & Egeth, 1989). However, later studies reported contradictory results (Shepherdson & Miller, 2014, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…Redundancy gain refers to the enhanced performance that arises when responses are based on multiple stimuli that converge on a single response, as opposed to a response based on a single stimulus. Although most of the evidence for this phenomenon is derived from relatively simple tasks, there is recent evidence that this phenomenon also applies to complex tasks, such as semantic categorization (Shepherdson & Miller, 2014). Redundancy gain would allow more efficient processing of the non-conflict trials, wherein responses based on multiple stimuli (beliefs and logic) converged on a single response.…”
Section: Discussionmentioning
confidence: 99%
“…van der Heijden, 1975). Indeed, Mullin and Egeth (1989) found support for the serial processing of words but the study of Shepherdson and Miller (2014;2016) came to a contradictory conclusion.…”
Section: Relation To the Prior Literaturementioning
confidence: 99%